Reforming the perceptions about reproductive health amongst adolescents in urban slums - Masare, Monika S.; Divekar, Sachin S.; Bhelkar, Sandeep M.; Hiwarkar, Prabhakar A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Adolescence is a transitional stage of physical and psychological development that generally occurs during the period from puberty to legal adulthood. It is marked by rapid physical growth and development with sexual maturity. The current study aims at assessing and reforming the perceptions affecting sexual behavior and attitude towards puberty, marriage, conception, STIs, HIV/AIDS and contraception among adolescent followed by appropriate training interventions. Methods: The study was conducted in an urban slum, on 110 adolescents of age 12 to 17 years in the field practice area of an urban health center in urban slum. A semi structured pretest and posttest Questionnaire administered to the study subjects with appropriate training interventions. The analysis was done using Microsoft Excel software. Results: Pretest showed that of only 19% of the adolescents could correctly mention half the physical changes occurring in boys during Puberty. Only 2% of the girls could mention the pubertal changes correctly. Awareness increased to up to 87% in boy’s and 51% in girls, who answered at more than half pubertal changes correctly in posttest respectively after teaching interventions. Perceptions about contraception, family planning STDs and HIV were also changed significantly after the interventions. Conclusions: Appropriate training about reproductive health is essential to sensitize the adolescents for the health empowerment at an early stage.